Advanced Methods of Fatigue Assessment - Radaj, Dieter; Vormwald, Michael (Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book in hand presents advanced methods of brittle fracture and fatigue assessment. The Neuber concept of fictitious notch rounding is enhanced with regard to theory and application. The stress intensity factor concept for cracks is extended to pointed and rounded corner notches as well as to locally elastic-plastic material behaviour. The averaged strain energy density within a circular sector volume around the notch tip is shown to be suitable for strength-assessments. Finally, the various implications of cyclic plasticity on fatigue crack growth are explained with emphasis being laid on the DJ-integral approach.   This book continues the expositions of the authors' well known reference work in German language 'Ermüdungsfestigkeit - Grundlagen für Ingenieure' (Fatigue strength - fundamentals for engineers).